Analisis Kinerja Pengurus dan Hubungannya dengan Partisipasi Anggota Koperasi di Kecamatan Tanjung Lago Kabupaten Banyuasin - Sriati Sriati; Henny Malini; Intan Trisna Dewi (Seminar Nasional Lahan Suboptimal, 2020)
Sriati S, Malini H, Dewi IT. 2020. Analysis of  management team performance and member participation of cooperative in tanjung lago sub district of Banyuasin tegency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The performance of the cooperative management team is one of the important factors for determining the performance of the cooperative, and one of the measures of cooperative performance is the member participatio, which is usually not match with quality expectation. The research aims to (1) measure and describe the performance of management team and participation of cooperative members  at Tanjung Lago Subdistrict, Banyuasin Regency, and (2) to analyze the relationship between management team performance and the participation of cooperative members at Tanjung Lago Subdistrict. The research was conducted at the Trans Mekar Sari Mandiri BMT Cooperative and Trans Damai Mandiri BMT Cooperative, using a survey method, and involving 43 respondents who were obtained by proportional stratification random sample method. Cooperative management team performance was measured by 5 indicators, namely the level of business development, member satisfaction, management services, management skills and implementation of the annual member meeting (RAT). Member participation was measured by indicators: member contributions in member meetings, contributions to paying dues, contributions of personnel and skills, contributions of ideas and contributions on decision making. The data were analyzed descriptively and the Spearman Rank correlation test was analyzed. The results showed that: (1) the performance of the cooperative management in Tanjung Lago District based on 5 variable indicators obtained an average score of 33.60 (74.67% of the ideal score) with moderate criteria, while the results of the analysis of the participation of cooperative members in Tanjung Lago Subdistrict based on 5 variable indicators obtain an average score of 30.35 (67.43% of the ideal score) including the criteria of being. (2) There is a significant positive correlation between the performance of cooperative management and the participation of cooperative members in Tanjung Lago Subistrict with a correlation coefficient of 0.750 ** at a = 0.05. Improving management performance and member participation could be conducted by extension and training method.